Influence of Co doping on combined photocatalytic and antibacterial activity of ZnO nanoparticles. (4th November 2016) - Anandan, M; Dinesh, S; Krishnakumar, N; Balamurugan, K
Abstract: The present work aims to investigate the structural, optical, photocatalyst and antibacterial properties of bare and cobalt doped ZnO nanoparticles (NPs) with different concentrations Zn1− x Co x O ( x  = 0, 0.03, 0.06 and 0.09) synthesized by co-precipitation method. The XRD patterns confirmed that all samples of cobalt doped ZnO nanostructures revealed the formation of single phase having hexagonal wurtzite structure with crystallite size in the range of 31–41 nm. Further, the decreasing trend in lattice parameters and grain sizes were also seen with increasing doping concentrations which confirms the incorporation of Co ions into the ZnO lattice. This result was further supported by the FT-IR data. HR-TEM images demonstrated the distinct hexagonal like morphology with small agglomeration. The UV–visible absorption spectra exhibits red shift with increase in Co doping concentration in ZnO while corresponding bandgap energy of cobalt doped ZnO NPs decreased with increased Co doping concentration. PL spectra showed a weak UV and visible emission band which may be ascribed to the reduction in oxygen vacancy and defects by cobalt doping. XPS and EDX spectral results confirm the composition and the purity of Co doped ZnO NPs. Furthermore, the Co doped ZnO NPs were found to exhibit lesser photocatalytic activity for the degradation of methyl green dye under UV light illumination in comparison with the bare ZnO NPs. Moreover, anti-bacterial studies reveals that the Co doped ZnO NPs possess more antibacterial effect against gram positive Basillus subtills and gram negative Klebsiella pneumoniae bacterial strains than the bare ZnO NPs.